Hambatan Pembelajaran Jarak Jauh bagi Guru Digital Immigrant - Yanti Tayo; Siti Nursanti; Wahyu Utamidewi (Jurnal Kebijakan Pembangunan, 2021)
The Ministry of Education and Culture has instructed the distance learning system (e-learning) to deal with the Covid-19 pandemic. E-learning must be implemented by all educational units without exception. This study aims to analyze the obstacles that occur during the implementation of e-learning. The type of research is descriptive qualitative. The primary data were collected directly from main sources through interviews with 4 Digital Immigrant Teachers at Pondok Ranggon 01 Pagi Elementary School, Cipayung District, DKI Jakarta. The results indicated that the Digital Immigrant Teachers at Pondok Ranggon 01 Pagi Elementary School were quite capable of doing the e-learning technology. However, when using E-learning platforms, some elements might be considered as obstacles in e-learning such as limited internet access and lack of proficiency in operating e-learning applications. Recommendations from this study on the implementation of e-learning increase literacy in the use of communication technology as part of the communication strategy for implementing government policies. Abstrak Kementerian Pendidikan dan Kebudayaan mengeluarkan kebijakan untuk menjalankan proses Pembelajaran Jarak Jauh (PJJ) yang harus diikuti seluruh guru dan murid di Indonesia tanpa terkecuali dalam rangka penanganan pandemi Covid-19. Penelitian ini bertujuan untuk menganalisis hambatan yang terjadi pada saat pelaksanaan PJJ. Penelitian ini dilakukan dengan pendekatan kualitatif. Data primer diambil melalui depth-interview kepada 4 orang guru digital immigrant di SD Pondok Ranggon 01 Pagi Kecamatan Cipayung DKI Jakarta. Hasil penelitian menunjukan guru digital immigrant di SD Pondok Ranggon 01 Pagi berhasil menerapkan dan beradaptasi dengan teknologi meskipun dibutuhkan literasi yang dilakukan secara berkesinambungan oleh pihak sekolah. Berbagai hambatan yang terjadi yaitu buruknya sinyal internet, keterbatasan kuota, serta kesulitan untuk menggunakan aplikasi yang disiapkan oleh pemerintah. Rekomendasi dari penelitian ini terhadap pelaksanaan PJJ meningkatkan literasi penggunaan teknologi komunikasi sebagai bagian dari strategi komunikasi pelaksanaan kebijakan pemerintah.